Human health risk assessment of ground water contaminated with petroleum PAHs using Monte Carlo simulations: A case study of an Indian metropolitan city - Rajasekhar, Bokam; Nambi, Indumathi M.; Govindarajan, Suresh Kumar (Journal of environmental management, 2018)
Underground pipelines are frequently used to transport petroleum fuels, through industrial as well as residential zones. Chennai is one of the four largest metropolitan cities of India. The region of interest in this study is located in the northern part of the Chennai. Ground water of this area was contaminated with polyaromatic hydrocarbons (PAHs) from the leaking oil storage tanks and pipe lines. Health risk assessment was conducted for exposure to PAHs in the ground water using incremental life time cancer risk (ILCR) models coupled with benzo[a]pyrene toxic equivalent method. The exposure pathways considered in this study were direct water ingestion and dermal contact under residential scenario. Exposure input parameters were transformed to statistical parameters using lognormal/uniform distributions and resultant probabilities of cancer risk were estimated by performing Monte Carlo simulations. Preliminary remediation goals were predicted using the combination of the cancer risk models of all the exposure routes with the consideration of high-safety risk of 1-in-1 million. Results showed that the cancer risk is predominantly contributed (greater than 98%) by dermal exposure than the oral in both adults and children. The total ILCR is found to be greater than a low safety risk of 1-in-10,000 with higher probability percentages (>90%). The 95th percentile values of the risk were presented in order to address the need for remediation. Appropriate remedial and treatment methods for the subject site were proposed. The results of the study will be useful for the regulatory boards and policy makers in India in understanding the actual impact of the contamination on receptors, setting up final remediation goals and deciding on a specific remedial method. •Monte Carlo simulations were applied for the health risk assessment.•Dermal exposure is contributing highly to cancer risk.•Adults are sensitive to cancer risk than children in all the exposure pathways.•A remediation goal of 99.5% removal of contamination is required.